STRATEGI BELAJAR KOSAKATA BAHASA INGGRIS (ENGLISH VOCABULARY) MAHASISWA TBI STAIN PAMEKASAN - Basri, Hasan; Rasyid Ridla, M.; Wahed, Abd. (OKARA: Jurnal Bahasa dan Sastra, 2014)
Vocabulary is crucial element in mastering a foreign language. knowing limited numbers of vocabulary will barry the students to communicate well in the traget language (English). As consequency, it takes some strategies to master it. The students get difficulity to master some kinds of vocabulary such as phrasal verb, idiom, slang and colloquial. Those matter makes them implement different learning Strategies to master. They are memory strategies, cognitive strategies, metacognitive strategies and compensation strategies. The most fasilitated strategies for learning and mastering vocabulary is through combining those various strategies